Hubungan Tingkat Kecemasan terhadap Penalty Shot Out pada Atlet Hockey Outdoor Putra Usia 21 Puslatcab Kota Surabaya - M Khoiril Anwar; Achmad Widodo (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Hockey is a joint or family sport consisting of two teams fighting against each other, by pitting the technique of maneuvering the ball into the opponent's goal with a tactical battle using sticks to play it. Tactical ability used to seek victory in a sporting manner when competing. Anxiety in the world of sports psychology has received special attention, but often in terms of anxiety it is equated with calm or stress even though these two things have different meanings but are interrelated. Anxiety can be experienced by everyone. It's just that the levels are different, Stress is a process in which a person prepares for threats and responds with a series of psychological and physiological changes. The population used was the hockey athlete at the Surabaya city branch of the training center, amounting to 20 hockey flies. The sampling technique in this study used a probability sampling technique with a sample of 18 outdoor hockey athletes at Puslatcab City of Surabaya, who were used as research subjects. The results of the discussion and analysis can be concluded that the penalty shoot out for Puslatcab athletes in the city of Surabaya significantly obtained a value of 0.904 > 0.482 and the relationship between variables was very positive which means that the lower the level of anxiety, the higher the success rate. the questionnaire scores of 17 athletes the lowest score is 13 and the average score is 16 for the highest score is 26, it can be seen that athletes who have the lowest level of anxiety when doing penalty shootouts are 5 (29.4%) athletes, athletes who have moderate levels of anxiety when 11 (64.7%) athletes took penalty shootouts, and 1 athlete (5.9%) who had a high level of anxiety when doing penalty shootouts.